2022
DOI: 10.3390/molecules27051602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Anticancer Activities of Microgreen Alga Chlorella vulgaris and Its Blend with Different Vitamins

Abstract: There is a very vital antioxidant extracted from microgreen alga. Chlorella vulgaris has major advantages and requires high yield worldwide. Some microalgae require vitamins for their growth promotion. This study was held to determine the impact of different vitamins including Thiamine (B1), Riboflavin (B2), Pyridoxine (B6), and Ascorbic acid (c) at concentrations of 0.02, 0.04, 0.06, and 0.08 mg/L of each. Each vitamin was added to the BG11 growth medium to determine the effect on growth, total carbohydrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The AE of Chlorella sorokiniana also showed high cytotoxicity (IC 50 = 59.21 ± 10.3 µg/mL) against the drug-resistant HCT-15 CRC line, although in this case, cytotoxic activity decreased (IC 50 = 165.41 ± 7.34 µg/mL) when the AE was obtained after a treatment with proteases (HP), indicating the possible contribution of a protein in the antiproliferative activity of this drug-resistant cell line. Our results are even more promising than those reported in the literature obtained with various extraction methods from different species of Chlorella [21,22,37]. Regarding the two archaea species analyzed, it should be noted that of the different extraction methods used, only the AE and HP showed antiproliferative activity against CRC cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The AE of Chlorella sorokiniana also showed high cytotoxicity (IC 50 = 59.21 ± 10.3 µg/mL) against the drug-resistant HCT-15 CRC line, although in this case, cytotoxic activity decreased (IC 50 = 165.41 ± 7.34 µg/mL) when the AE was obtained after a treatment with proteases (HP), indicating the possible contribution of a protein in the antiproliferative activity of this drug-resistant cell line. Our results are even more promising than those reported in the literature obtained with various extraction methods from different species of Chlorella [21,22,37]. Regarding the two archaea species analyzed, it should be noted that of the different extraction methods used, only the AE and HP showed antiproliferative activity against CRC cells.…”
Section: Discussionsupporting
confidence: 68%
“…A methanolic extract of this microalga was tested on hepatocellular carcinoma (HEPG-2), human prostate cancer (PC-3) and colorectal cancer (HCT-116) cell lines. The data obtained show that for the colorectal cancer line there was an inhibition of cell growth of around 70% at a dose of 100 µg/mL [21]. The ethanolic extract of Chlorella vulgaris has also been studied in vitro in lung (A549), breast (MCF7), cervical (Hela), and hepatocellular (Huh7) cancer cell lines, showing an inhibition of cell growth in all lines tested [22].…”
Section: Introductionmentioning
confidence: 91%
“…Carotenoids and epigallocatechin gallate have been identified in studies using the applied extract [ 97 ]. Ragaa A. Hamouda et al demonstrated the anti-cancer effect of methanol extract from chlorella on HCC [ 98 ]. In animal studies with developed non-alcoholic fatty liver disease, alga supplementation improved the insulin sensitivity and lipid profile and reduced inflammation [ 99 ].…”
Section: Selected Food Products With Hepatoprotective Propertiesmentioning
confidence: 99%
“…Animal and in vitro studies have shown its antiproliferative effects on liver and colorectal cancer cells [6,7]. Lycopene isolated from chlorella inhibited the growth of prostate cancer cells in [64]. In an animal model, chlorella extract reduced bone marrow suppression caused by cisplatin [8].…”
Section: Chlorellamentioning
confidence: 99%